Analisis Pengaruh Pergaulan Antar Rekan Sebaya terhadap Ketidaksantunan Berbahasa Siswa di Lingkungan SMPN 50 Batam: Ketika Lingkungan Pergaulan Membentuk Cara Bicara Kasar - Ara, Cahyati; Meilani Putridamayanti; Elisabet Nababan; Suryani; Fabio Tasty Ariance Loren (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the influence of peer interaction on impolite language behavior among students of SMPN 50 Batam. Using a qualitative case study approach, this study collected data through observation and documentation to understand how peer interaction shapes rude language habits among students. The results of the study indicate that social interactions in peer interaction significantly contribute to the emergence of impolite language behavior, including the use of rude language as a form of expression and adjustment in groups. A social environment that does not emphasize politeness norms leads to an increase in the frequency of impolite language behavior, which has a negative impact on students' social relationships at school. This study emphasizes the importance of character development and the active role of schools and families in creating an environment that supports polite language.